Trichodina Sp. as Bioindicator for Evaluation of Biochemical Oxygen Demand (Bod5) in Aquaculture Fish Farms (Ponds) - Al-Marjan, Karwan Sallo Najm; Abdullah, Shamall M.A. (Science Journal of University of Zakho, 2015)
The present study include the using of the prevalence of the fish infestation by the protozoan Trichodina sp. as bioindicator for evolution of the biological oxygen demand BOD5 (lowering down of the dissolved oxygen DO) from Ainkawa fish hatchery. For this purpose, two handered and fourty (240) finger ling fishes of Cyprinus carpio were collected from six ponds (40 samples from each pond) and fishes were examined from December, 2012 to the end of february, 2013. Biological oxygen demands were measured by azid modification of Winkler method (through measuring of dissolved oxygen DO) for each pond. Results reveal that there are a direct relationship between the prevalence of fish infestation by the Trichdina sp. and the values of BOD5. The prevalence of fish infestation in each pond increased (57.5, 40, 27.5, 45, 15, and 42.5% respectively) with the increase of the values of BOD5 (9.2 , 8.0, 5.7, 8.1, 2.9 and 8.0 mg.l-1, respectively).